Extrapolation of operators acting into quasi-Banach spaces. (11th March 2016) - Lykov, K V
Abstract: Linear and sublinear operators acting from the scale of L_p spaces to a certain fixed quasinormed space are considered. It is shown how the extrapolation construction proposed by Jawerth and Milman at the end of 1980s can be used to extend a bounded action of an operator from the L_p scale to wider spaces. Theorems are proved which generalize Yano's extrapolation theorem to the case of a quasinormed target space. More precise results are obtained under additional conditions on the quasinorm. Bibliography: 35 titles.